Lymphadenopathy and severe infection caused by cytomegalovirus: algorithm for the diagnosis and treatment of lymphoproliferative disease (clinical case) - G. Kh. Vikulov; I. V. Oradovskaya; D. S. Konnov; I. V. Barysheva (LLC "Diagnostics and Vaccines", 2020)
Objective: to analyze a clinical case and improve early and timely diagnosis of lymphomas, focusing on an interdisciplinary approach in the management of patients with lymphoproliferative syndrome and herpesvirus infections.The article describes the current aspects and difficulties of the differential diagnosis of lymphadenopathy in clinical practice, the clinical case of T-cell lymphoma.Based on the history, complaints, clinical presentation, and results of the examination, a 13-year-old child was diagnosed with ALK-positive anaplastic large cell lymphoma, stage III, with damage to the lungs, intrathoracic, intra-abdominal lymph nodes, pancreas, and skin. In this clinical case, the development of reactivated manifest cytomegalovirus infection of severe course in conditions of deep immunosuppression is given. An algorithm for the diagnosis and successful treatment of lymphoma and cytomegalovirus infection is described, which is important for the clinical practice of a pediatrician, an infectious disease specialist, a clinical immunologist-allergist, and hematologist.